Toxocarpus incarnatus (Apocynaceae, Secamonoideae), a new species from Thailand - Kidyoo, Aroonrat (Phytotaxa, 2022)
Toxocarpus incarnatus A. Kidyoo, newly described here, is a twining climber growing in disturbed evergreen forest in western Thailand. A diagnosis and detailed description of this new species, as well as photographs are provided. Several characters of T. incarnatus are compared with those of T. oblanceolatus, considered to be a close relative. These two species display consistent differences in leaf shape, flower color and characters of the style-head. In addition, a comparison with other species, T. concanensis and T. spirei, is also provided.